Organic Waste Diversion in Atlantic Canada - Vanderkloet, Rachel (Université d'Ottawa | University of Ottawa, 2023)
Sustainable waste management is essential for reducing greenhouse gas emissions, conserving landfill space, and producing valuable end-products. Organic waste diversion plays an important role in sustainable waste management with various environmental and economic benefits. Organic waste diversion is not a new concept, and many areas have had systems in place for over 20 years. One area where there are significant variations in residential organics waste diversion rates is Atlantic Canada. This research paper investigates the factors that contribute to these variations and explores the barriers and opportunities for increasing diversion across the region. Through a comprehensive literature review, the study investigates several factors that may affect diversion rates, including population density, access to composting facilities, curbside collection, and public education and outreach programs. The paper explores unique challenges in organics waste diversion in rural areas of Atlantic Canada due to limited access to resources and infrastructure. The study also highlights various opportunities for progress, such as increased funding for diversion programs and more data collection and reporting on waste management. Overall, this research paper provides insights for policymakers and practitioners looking to improve diversion rates and advance sustainable waste management practices in Atlantic Canada.